High-Quality Whispering-Gallery-Mode Lasing from Cesium Lead Halide Perovskite Nanoplatelets - Zhang, Qing (2017)
Semiconductor micro/nano-cavities with high quality factor (Q) and small modal volume provide critical platforms for exploring strong light-matter interactions and quantum optics, enabling further development of coherent and quantum photonic devices. Constrained by exciton binding energy and thermal fluctuation, only a handful of wide-band semiconductors such as ZnO and GaN have stable excitons at room temperature. Metal halide perovskite with cubic lattice and well-controlled exciton may provide solutions. In this work, high-quality single-crystalline cesium lead halide CsPbX3 (X = Cl, Br, I) whispering-gallery-mode (WGM) microcavities are synthesized by vapor-phase van der Waals epitaxy method. The as-grown perovskites show strong emission and stable exciton at room temperature over the whole visible spectra range. By varying the halide composition, multi-color (400–700 nm).WGM excitonic lasing is achieved at room temperature with low threshold (~ 2.0 μJ cm−2) and high spectra coherence (~0.14–0.15 nm). The results advocate the promise of inorganic perovskites towards development of optoelectronic devices and strong light-matter coupling in quantum optics.